Chimerism, Transplant Tolerance, and Beyond. Issue 8 (August 2019) - Messner, Franka; Etra, Joanna W.; Dodd-o, Jeffrey M.; Brandacher, Gerald
Abstract : The present review discusses current developments in tolerance induction for solid organ transplantation with a particular emphasis on chimerism-based approaches. It explains the basic mechanisms of chimerism-based tolerance and provides an update on ongoing clinical tolerance trials. The concept of "delayed tolerance" is presented, and ongoing preclinical studies in the nonhuman primate setting—including current limitations and hurdles regarding this approach—are illustrated. In addition, a brief overview and update on cell-based tolerogenic clinical trials is provided. In a critical approach, advantages, limitations, and potential implications for the future of these different regimens are discussed.